Teachers’ Strategies to Enhancing Reading Skill as The Base Components for Multilingual Invants in The Classroom - Azdmi, Maulycya Sierly Ullul (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
English has the prominent role in the society. As taught in recent cases the language implied their characteristics in any evidences. Moreover, English for Foreign Learner (EFL) have adapted to learn and produce something available for the future. This research have presented along the community where the writer intended for study. Applied linguistics were exporting in English Second Language (ESL) which determining the application of Technological Pedagogical Content Knowledge (TPACK). The paper is using multilingualism and English Language Teaching (ELT) as the study objects through Target Text (TT) and Source Text (ST). To determine the discussion and finding, the writer intended in library research with qualitative study, open-ended questions, and analytical methods. As the final results, there will be teacher strategies to apply some plans and general introductions for L2 learner in Indonesia.